A new species and records of Alepia Enderlein (Diptera, Psychodidae, Psychodinae) from Argentina - Omad, Guillermo; Rossi, Gustavo C. (Zootaxa, 2012)
A new species of Neotropical Psychodidae, Alepia claritae sp. nov., is described from Argentina. Specimens were col-lected in a Malaise trap located in Misiones Province. Based on material from the same locality, we include a re-descrip-tion of the adult male of Alepia copelata Quate (1999), previously known from Barro Colorado Island, Panama. These arethe first records of Alepia and the sixth record of a psychodine species for the Neotropical region of Argentina. A list of the non-phlebotomine Psychodidae for Argentina is included.